Informe de pasantía en la cámara de Comercio e Industria Colombo Chilena Pasantía Cámara Colombo Chilena Fortalecimiento Comercial a empresas de la Alianza del Pacífico (2022)
In this report, the study of different foreign trade indicators was carried out during the last ten years for the countries that make up the Pacific Alliance (PA), Colombia, Chile, Mexico and Peru, in order to establish the relationship between growth and development. of these countries, with the contributions made by the Colombo-Chilean Chamber of Commerce and Industry, an entity that promotes commercial relations between the PA countries, through the provision of communication and information tools that it puts at the service of Your clients. Given the above, the data was collected, and it was found that the PA is not competitive at the intra-regional level, since it has a trade deficit since its creation to date and although it has very similar economic structures, this is not enough to give way to a greater level of openness with other regions such as Asia-Pacific, which is one of the most relevant objectives of the PA. Taking into account the current situation of the PA, the Colombo-Chilean chamber has been implementing different services that allow the support of the commercial relations of these countries at an intra-regional level, however, it is not taking into account the objectives of the PA, since it would be It is convenient to start implementing its services in such a way that it can be the creator of strategies and commercial relations with Asian companies, for example in Singapore, taking into account that this country recently signed an agreement with the PA. As a result of the above, the DOFA matrix was carried out, which allows a real-time diagnosis of the state of the chamber in terms of its weaknesses, opportunities, strengths and threats internally and externally, finding that it must improve processes and tools and implement means that allow greater recognition at the regional level.